The challenges and legislative novelties related to electronic evidence (Academic Journal of Internal Affairs, 2019)
The aim of the publication is to introduce the challenges and legislative novelties related to electronic evidence. Firstly, it focuses on the current Hungarian Criminal Procedure Law’s provisions on seizure of electronic data. Then it continues with the new proposal for regulation on cross-border access to e-evidence at EU level. Finally, it deals with the encryption related issues in the criminal proceedings with special regard to prohibition of self-incrimination.
Keywords: electronic evidence; seizure of electronic data; cryptocurrencies; encryption